Development and evaluation of a micro-cogeneration prototype for residential applications - Ferreira, Ana C. M. (2012)
Combined heat and power (CHP) units use heat that would otherwise be wasted in a conventional power plant, and may reach an overall efficiency above 90% (LHV), which is well above to the 40% achieved by reference plants. This paper presents the design and development of a micro- cogeneration prototype (<6kWe) for single-family households. The unit is based on a commercially available internal combustion engine (ICE) and generator, optimized and modified to be fuelled by natural gas, coupled to a two-step exhaust heat recuperating system. The work starts with the thermodynamic analysis of the ICE operating cycle and the assessment of thermal energy that can be recovered from the exhaust gases and through the engine cooling system. The analysis included the study of gas-mixture composition, combustion, heat loss to engine walls and water- vapour mass transfer. The main innovation is the exhaust gases heat recovery system, developed in two stages. The first stage consists on a direct heat exchanger where water is heated by direct contact with hot jets of exhaust gases, while the second stage heat exchanger involves further cooling of the saturated gases and condensation of evaporated water. The results showed the potential for significant gains in engine performance. The effective thermal power recovered in the recuperating system is reasonable, since the CHP system is able to produce 6.58 kWe of electrical energy and 16 kW of thermal energy.